(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
In the article, the main concept of blessing is the accumulation of strength by receiving the support of invisible forces and oneself, as well as possessing the power of creation, this Holy Power is considered the greatest blessing. Bata is a custom of wishing good luck to a person who has lived among the Kyrgyz people since ancient times. A curse is the opposite of a blessing. Cold words of reverse blessing (curse) pierce the human heart and pass through the bones. This is a verbal formula that wishes harm to a person.Key words: life, blessing, curse, oath, goodness, evil, dialectic analysis.